High Sensitivity Electrothermal Actuation-based CMOS-MEMS Relative Humidity Sensor - Ahmed, A. Y.; Witjaksono, G.; Dennis, J. O.; Md Khir, M. H.; Rabih, Almur. A. S.; Mian, Muhammad. U.; Ahmed, Mawahib. G. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents a high sensitivity CMOSMEMS humidity sensor based on electrothermal actuation for application in indoor relative humidity monitoring. The detection is based on the principle of amplitude change as a result of absorption/adsorption or desorption of the humidity molecules onto the surface of a titanium dioxide (TiO2) active material deposited on a moving plate of the sensor resulting into a change of its mass. The CMOS-MEMS humidity sensor measurement is performed after preconditioning in which the sensor goes through early actuation before the real measurement is done. The sensor is operated in the dynamic mode at an actuation input frequency of 2 Hz and a driving voltage varied from 2 Vpp to 6 Vpp. The maximum output voltage observed was at 4 Hz, which is double the input frequency. The voltage was found to increase linearly from 8.728 mV to 71.117 mV with the increase in driving voltage from 2 Vpp to 6 Vpp. The response of the device to humidity shows linear output voltage change from 66.998 mV to 69.822 mV when relative humidity increases from 40% RH to 60% RH with a sensitivity of 0.14 mV/% RH.